2019
DOI: 10.1080/15548627.2019.1606647
|View full text |Cite
|
Sign up to set email alerts
|

MTORC1 coordinates the autophagy and apoptosis signaling in articular chondrocytes in osteoarthritic temporomandibular joint

Abstract: A switch from autophagy to apoptosis is implicated in chondrocytes during the osteoarthritis (OA) progression with currently unknown mechanism(s). In this study we utilized a flow fluid shear stress (FFSS) model in cultured chondrocytes and a unilateral anterior crossbite (UAC) animal model. We found that both FFSS and UAC actively induced endoplasmic reticulum stress (ERS) in the temporomandibular joints (TMJ) chondrocytes, as demonstrated by dramatic increases in expression of HSPA5, p-EIF2AK3, p-ERN1 and AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
175
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(185 citation statements)
references
References 57 publications
(75 reference statements)
10
175
0
Order By: Relevance
“…*P < 0.05, **P < 0.01, and ***P < 0.001 vs. FSS + IFT88-siRNA group. Zhang et al, 2018;Yang et al, 2019). In line with previous studies, our data demonstrated that moderate FSS activated autophagy in NP cells by increasing the ratio of LC3-II to LC3-I, the protein expression of Beclin-1 and the number of autophagosomes and autolysosomes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…*P < 0.05, **P < 0.01, and ***P < 0.001 vs. FSS + IFT88-siRNA group. Zhang et al, 2018;Yang et al, 2019). In line with previous studies, our data demonstrated that moderate FSS activated autophagy in NP cells by increasing the ratio of LC3-II to LC3-I, the protein expression of Beclin-1 and the number of autophagosomes and autolysosomes.…”
Section: Discussionsupporting
confidence: 92%
“…The cells were cultured in Dulbecco's Modification of Eagle's Medium (10-013-CVR; Corning, United States) containing 10% FBS (10099-141; Gibco, Australia) supplemented with 1% penicillin-streptomycin (SV30010; Hyclone, United States) at 37 • C with 5% CO 2 . FSS experiments were conducted as previously described (Yang et al, 2019). Cells were seeded onto collagen I-coated culture slips (75 mm × 25 mm × 1 mm; FFCS-C; Flexcell, United States) at a density of 3.0 × 10 4 /cm 2 and incubated in a 5% CO 2 incubator at 37 • C. When cells reached up to 85% confluence, the slips were then placed in a parallel plate flow chamber of Streamer R System (STR-4000; Flexcell, United States) ( Figure 1B) and cells are exposed to 12 or 24 dyne/cm 2 FSS for 0, 1, 2, 3, and 4 h. For certain experiments, NP cells were pre-treated with 10 µM CoPP (Sigma, United States, C1900) for 1 h or 500 nM rapamycin (Selleck, United States, S1039) for 12 h before exposure to FSS.…”
Section: Np Cell Line Culture and Fss Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the catabolic pathway, forkhead box class O-3, (1,3,52,54) muscle atrophy F-box, (1,3) muscle ring-nger protein-1 (1,3,52) and nuclear factor kappa-beta (1,3) will be measured. For information about autophagy, ULK1, (54,55) light-chain 3 (55,56) and p62 (55,56) will be analysed. For an overview of enzyme regulation, AMP-activated protein kinase (8,25,(53)(54)(55) will be studied.…”
Section: Con Dentialitymentioning
confidence: 99%
“…For the catabolic pathway, forkhead box class O-3, (1,3,35,37) muscle atrophy F-box, (1,3) muscle ring-finger protein-1 (1,3,35) and nuclear factor kappa-beta (1,3) will be measured. For information about autophagy, ULK1, (37,38) light-chain 3 (38,39) and p62 (38,39) will be analysed. For an overview of enzyme regulation, AMP-activated protein kinase (6,23,(36)(37)(38) will be studied.…”
Section: Assessment Of Primary Outcome Measurementioning
confidence: 99%